ANALISIS KESIAPAN PELAKSANAAN KEGIATAN PEMBELAJARAN TATAP MUKA DI INDONESIA PADA TAHUN 2021 - Muhammad Marshal Nugroho; Amarrakhaisya Syamsuar; Ameerakhaiya Syamsuar; Hafizh Muhammad Anfasha Yunaryo; Lintang Ambar Pramesti; Ma'ruf Nurrudin; Muhammad Alif Darmamulia; Rachiny Anantridha Fasya; Salsabilla Husna Haniffah; Sanjika Ilham Putra Lumban Gaol; Ernawati Ernawati (Journal Publicuho, 2020)
The COVID-19 pandemic affects almost every aspect. The level of spread and the high number of positive cases force humans to adapt to prevent the spread of the COVID-19 virus. The education aspect is one of the aspects affected by COVID-19. As a result, the learning process is carried out online to prevent the spread of COVID-19. In practice, there are still some deficiencies in the online learning process in Indonesia. These deficiencies are supporting factors such as uneven internet connections or socio-economic class differences that can cause differences in the level of acceptance of knowledge between students. Thus, it has been considered by the government to carry out an offline learning process. The plan for implementing face-to-face learning activities will start in January 2021. Of course, some preparations must be made by the government and the community before implementing offline learning. Based on the research that has been done, it is concluded that the government and the community must prepare human resources, prepare facilities and infrastructure, administer licensing, and carry out the COVID-19 vaccine immunization sequentially.